Urban design, public space and creative milieus: an international comparative approach to informal dynamics in cultural districts - Costa,Pedro (2013)
This paper explores the relation between urban design, public space appropriation and the informal dynamics taking place on creative milieus, from an international comparative perspective. Based on an empirical approach to urban morphology, everyday life and symbolic public space appropriation on those areas, ten cultural quarters around the world are studied: Bairro Alto (Lisbon); La Gracia (Barcelona); Vila Madalena (São Paulo); Beyoglu (Istanbul); Marais (Paris); Oltrarno (Florence); Akihabara (Tokyo); Kreuzberg SO36 (Berlin); Capitol Hill (Seattle); and Brick Lane (London). They represent very diverse situations in terms of their historical, cultural and economic backgrounds as well as in what concerns the spatial conditions that support creative clusters and the vitality and sustainability of creative milieus. Drawing on literature review and on the recollection and critical interpretation of visual information on these areas, a comparative approach to these cases is developed, considering multiple analytical dimensions, which enable us to map and characterize the diversity of urban cultural districts. This may provide a contribution towards the development of a new planning agenda for dealing with urban creative dynamics and cultural quarters.